Androgen receptor antagonist flutamide modulates estrogen receptor alpha expression in distinct regions of the hypospadiac rat penis - Elmelund, Emilie; Draskau, Monica K.; Berg, Marie; Strand, Ida W.; Black, Jay R.; Axelstad, Marta; Pask, Andrew J.; Svingen, Terje (Frontiers in Endocrinology, 2025)
IntroductionIntrauterine exposure to endocrine disrupting chemicals (EDCs), particularly anti-androgens, has been implicated in hypospadias by disrupting fetal masculinization of the genital tubercle (GT). Other pathways, including estrogen signaling, may also contribute but remain poorly characterized, especially in rats – a key model in chemical toxicity testing. Estrogen signaling has also been linked to hypospadias in mice, raising questions about androgen-estrogen interactions in guiding GT differentiation. MethodsWe induced hypospadias in male rat offspring via intrauterine exposure to the antiandrogenic drug flutamide and characterized androgen and estrogen receptor expression.ResultsWe observed key structural and transcriptional changes in the developing penis, including altered estrogen receptor a (ERa, Esr1) expression. Notably, beyond this established androgen-estrogen relationship in hormone-sensitive tissues, anti-androgenic exposure also induced spatial changes in Esr1 expression in specific regions of the GT.DiscussionFuture toxicological testing using new approach methodologies (NAMs) should consider androgen-estrogen balance and crosstalk in reproductive tissues as a mechanism of action.